The New World Economy A Beginner's Guide : Demystifying Everything from AI and Bitcoins to Unicorns and Generation Z - Epping, Randy Charles (VINTAGE BOOKS, 2020)
"What is blockchain? What is Bitcoin? How can central banks be instrumental in guiding a nation's economy? What are the underlying causes of trade deficits? Do trade wars actually help the domestic economy? How has the behavior of millennials and Generation Z affected the global economy? Find out all this and more in this definitive guide to the world economy. As the global economic landscape shifts at an increasing rate, it's more important than ever that citizens understand the building blocks of the new world economy. In this lively guide, Randy Charles Epping cuts through the jargon to explain the fundamentals. In thirty-six engaging chapters, Epping lays bare everything from NGOs and nonprofits to AI and data mining. With a comprehensive glossary and absolutely no graphs, The New World Economy: A Beginner's Guide is essential reading for anyone who wants to understand what is going on in the world around them. This timely book is a vital resource for today's chaotic world"